2016
DOI: 10.21270/archi.v5i2.1317
|View full text |Cite
|
Sign up to set email alerts
|

Displasia cemento-óssea florida: relato de caso

Abstract: Lesões fibro-ósseas benignas são caracterizadas pela substituição do tecido ósseo normal por tecido conjuntivo fibroso celular com conteúdo calcificado variando distribuição e volume. A displasia cemento-óssea florida não tem etiologia definida, prevalecendo em mulheres negras de meia idade a idosas. Pode se expandir bilateralmente, mostra-se restrita aos maxilares e envolve a região periapical dos dentes com vitalidade pulpar. Na maioria dos casos a lesão é descoberta entre os 30 e 50 anos de idade durante ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Due to this risk of postoperative infection and because it is a bone pathology that, in most cases, does not require treatment, the diagnosis of COD should be based only on clinical and imaging assessment. 9 Previous studies have highlighted the importance of CBCT for the diagnosis, assessment, and monitoring of COD because it allows greater accuracy in visualizing this fibro-osseous lesion and its relationship with adjacent anatomical structures, which is essential to choose the adequate therapy and prevent exposure of avascular mineralized tissue in the oral cavity and consequent infection. 5,6 As previously described, 5,6 in the present case, CBCT helped identify expansive and aggressive features of FLCOD, such as external root resorption in the right maxillary first molar, bone expansion, and cortical rupture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to this risk of postoperative infection and because it is a bone pathology that, in most cases, does not require treatment, the diagnosis of COD should be based only on clinical and imaging assessment. 9 Previous studies have highlighted the importance of CBCT for the diagnosis, assessment, and monitoring of COD because it allows greater accuracy in visualizing this fibro-osseous lesion and its relationship with adjacent anatomical structures, which is essential to choose the adequate therapy and prevent exposure of avascular mineralized tissue in the oral cavity and consequent infection. 5,6 As previously described, 5,6 in the present case, CBCT helped identify expansive and aggressive features of FLCOD, such as external root resorption in the right maxillary first molar, bone expansion, and cortical rupture.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 As FLCOD does not require treatment and its diagnosis can be performed only with clinical and imaging examinations, some authors do not recommend biopsy due to this lesion's avascular characteristics, which could increase the risk of osteomyelitis after surgical procedures. 9 Elective surgeries, such as implant placement, are contraindicated due to the increased risk of bone infection and osseointegration failure. 10 On the other hand, studies have demonstrated success in dental implant placement in areas close to the fibro-osseous lesion, offering a possibility to patients affected by FLCOD.…”
Section: Introductionmentioning
confidence: 99%
“…Vários tipos de lesões fibro-ósseas-maxilo-faciais apresentam uma característica bastante comum, qual seja, a substituição de osso normal por tecido conjuntivo. Este tecido conjuntivo, entretanto, apresenta características distintas de um tecido conjuntivo fibroso normal, ou seja, trata-se um misto de tecido mineralizado formado por osso maduro, osteoide e cementoide, isto é, calcificações semelhantes ao cemento (MORETI L, et al, 2016).…”
Section: Discussionunclassified